2012
DOI: 10.1007/s00125-012-2620-3
|View full text |Cite
|
Sign up to set email alerts
|

Low HbA1c and mortality: causation and confounding

Abstract: This commentary provides an overview of the clinically important data linking low or lowered HbA 1c to increased total and CVD mortality in the general population, and in patients with diabetes. This sets the scene for a contribution in this issue of Diabetologia by Andersson et al

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 31 publications
3
22
1
Order By: Relevance
“…Findings compared with previous studies Recent trials have found that intensive glucose control is associated with increased risk of cardiovascular death in younger patients [8] and observational studies have generally demonstrated Ushaped relationships between levels of HbA 1c in diabetic patients and death [28,29], possibly attributable to residual confounding through unmeasured variables [12]. In our study we adjusted for several important confounders, including comorbidities such as heart failure, chronic obstructive airways disease and chronic kidney disease.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Findings compared with previous studies Recent trials have found that intensive glucose control is associated with increased risk of cardiovascular death in younger patients [8] and observational studies have generally demonstrated Ushaped relationships between levels of HbA 1c in diabetic patients and death [28,29], possibly attributable to residual confounding through unmeasured variables [12]. In our study we adjusted for several important confounders, including comorbidities such as heart failure, chronic obstructive airways disease and chronic kidney disease.…”
Section: Discussionmentioning
confidence: 80%
“…Similarly, BP control below 130/ 80 mmHg was recently found not to reduce all-cause mortality in newly diagnosed diabetes patients [11]. Other studies demonstrated a U-shaped relationship between HbA 1c levels and all-cause mortality, which is possibly attributable to residual confounding through unmeasured variables [12]. For example, patients in the later stages of cancer often have low plasma glucose levels, where the elevated risks of adverse outcomes are due to the cancer not the hypoglycaemia.…”
Section: Introductionmentioning
confidence: 97%
“…Based on the squared difference of the measurements to their average value, the approach would seem to amplify large differences. The difficulty in the definition and interpretation of HbA 1c variability has been noted by several authors [15,16]. Our approach provides a partial but imperfect solution to these problems; while accounting for the length of time between measurements, the variance of our statistic may be higher with widely spaced measurements.…”
Section: Discussionmentioning
confidence: 98%
“…The RIACE study group found no association between HbA 1c variability and myocardial infarction or stroke [13] Here, CVD was defined more widely, including, for example, myocardial infarction, heart failure and non-fatal ischaemic stroke [10]. Interestingly, the recent literature is quite inconsistent about the relationship between the effect of low HbA 1c and the risk of mortality or CVD [15]. Various studies demonstrated a consistent positive linear relationship between HbA 1c and the risk of mortality or CVD [29,30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation